2017
DOI: 10.5376/jmr.2017.07.0010
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Insecticide Resistance to Temephos, and Associated Mechanisms in <i>Culex pipiens</i> Mosquitoes from Central Tunisia

Abstract: Five populations of Culex pipiens collected in central Tunisia were evaluated for their susceptibility to temephos. The resistance level was high for samples # 5 (>50-fold), and low, not exceeding 4-fold in the other resistant samples. LC 50 showed the susceptibility of sample # 2. The CYP450 enzyme was found related to temephos resistance in three samples. In fact, the addition of Pb to temephos bioassays completely suppressed the resistance in samples # 1 (RR 50 =0.84, p>0.05, RSR=3.0) and 5 (RR 50 =1.5, p>0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the present study, both chemical and synergism tests did not revealed any over-produced esterases to be involved in the recorded resistance to OPs insecticides. These detoxification enzymes were involved in the resistance to chlorpyrifos and temephos insecticides in Tunisian Culex pipiens 14,21,22. This correlation was found also in other mosquito's species including Aedes aegypti 15.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, both chemical and synergism tests did not revealed any over-produced esterases to be involved in the recorded resistance to OPs insecticides. These detoxification enzymes were involved in the resistance to chlorpyrifos and temephos insecticides in Tunisian Culex pipiens 14,21,22. This correlation was found also in other mosquito's species including Aedes aegypti 15.…”
Section: Discussionmentioning
confidence: 57%